Quality Function Deployment Application Based on Interval 2-Tuple Linguistic - Zhen Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The application of quality function deployment method can meet the customers’ requirement, and optimize the enterprise product design. Based on the house of product design, the paper adopts the interval two-tuple linguistic model and possibility theory, and constructs the correlation matrix of product design and customer requirement for cars, then the important sequence of design elements: engineer oil consumption, vehicle size, fuel consumption design and transmission type are the main elements in the automobile design.